Relationship Between Communication Satisfaction And Organizational Identification: A Upm Case Study - Mustafa Kamal, Daniel Kamal; Hasan, Hamisah; Abdul Muati @ Zamri Ahmad, Abdul Muati @ Zamri Ahmad (2015)
This study examined the relationship between organizational identification and communication satisfaction. Communication satisfaction was represented by seven dimentions: Organizational Perspective, Personal Feedback, Organizational Integration, Supervisory Communication, Horizontal Communication, Media Quality, and Communication Climate .The present study employed a quantitative approach by utilizing a self-administered survey questionnaire. Data was collected using two established instruments, the Downs and Hazen’s Communication Satisfaction Questionnaire (CSQ) and the Mael’s Scale for Organizational Identification (MOI).